Prolonged diagnostic journey and follow-up of a patient with Behçet’s disease in infectious disease practice - O. A. Lyubimtseva; I. V. Savelyeva (Rheumatology Science and Practice, 2026)
Behçet‘s disease (BD) is a rare systemic vasculitis with multiorgan manifestations and an unclear etiology. The difficulty in early diagnosis due to clinical polymorphism and the absence of pathognomonic markers leads to delayed treatment, disability, and a worse prognosis. This article demonstrates the diagnostic and therapeutic challenges of BD using the clinical case of patient M., 41 years old, as an example. The importance of an interdisciplinary approach and early initiation of immunosuppressive therapy is emphasized.